SEMA3B is associated with disease activity and infliximab response in IBD patients but does not contribute to the development of intestinal inflammation in vivo - Arosa, Laura; Malvar-Fernández, Beatriz; Antúnez-López, José; García, Samuel; Conde-Aranda, Javier (Frontiers in Immunology, 2026)
BackgroundInflammatory bowel disease (IBD) is a chronic inflammatory disorder with increasing worldwide incidence and prevalence. While current treatment options alleviate part of the socioeconomic burden of this disease, new biomarkers and safer therapeutic approaches are needed to combat intestinal inflammation. Class-3 semaphorins (sema3A-3G) have emerged as important regulators of some biological functions underlying inflammation. For instance, SEMA3B protects against tissue damage in arthritis. However, the association of this protein with UC and its involvement in the onset of intestinal inflammation remains elusive.MethodsTo close that knowledge gap, we performed a comprehensive transcriptomic analysis of different patient cohorts. Moreover, we investigated the therapeutic efficacy of Sema3B in vivo.ResultsOur findings revealed that the expression of SEMA3B was downregulated in IBD patients compared with healthy controls. Similarly, non-responder UC patients to infliximab showed reduced transcript levels of that class-3 semaphorin before receiving the treatment. Unfortunately, the administration of recombinant Sema3B to mice subjected to DSS-acute colitis did not modify the course of the disease.ConclusionsTherefore, SEMA3B appears to be an interesting biomarker in the context of intestinal inflammation, which deserves further validation in larger cohorts. Nonetheless, based on our in vivo results, the implication of this factor in the development of colitis seems to be minimal.